Ethnic Conflict Between Mandailing and Minangkabau in Padang Lawas Regency: Background, Drivers, and Management Strategies - Nur Khadijah Nasution; Dahlia Lubis; Endang Ekowati (Yayasan Bayt Shufiya Nusantara, 2026)
This article aims to explain the causes of social conflict between the Mandailing and Minangkabau ethnic groups in Padang Lawas. It raises two main questions: what are the causes of the conflict, and how is the conflict managed? This study employs a qualitative approach with a field research design, while the data were collected through observation, interviews, and documentation. The findings show that the conflict stems from clashes in communication culture, cultural differences, acculturation in interethnic marriages, and domination of the economic sphere as sources of intergroup tension. As a result, equal and dialogical social integration has failed to develop. In certain contexts, the Minangkabau ethnic group, as migrants, is perceived as not having fully assimilated into the local customs and culture of the Mandailing community, thereby creating social distance, prejudice, and stereotypes that continue to be reproduced in everyday interactions. On the other hand, interethnic marriage often becomes an arena of identity negotiation laden with cultural pressures, while domination in the economic sector further reinforces social boundaries between the two groups. This article emphasizes that social conflict in a plural society is not merely the result of ethnic difference itself, but rather the product of disrupted communication, fragile acculturation, and unequal power relations. Therefore, conflict resolution requires a more transformative cultural approach through cultural dialogue, the strengthening of social empathy, and the reconstruction of more inclusive interethnic relations. These findings demonstrate that without fair management of pluralism, diversity can easily shift from being a social asset into a latent source of social fragmentation.